2020
DOI: 10.1007/s00432-020-03404-6
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific antibodies targeting dual tumor-associated antigens in cancer therapy

Abstract: Purpose Bispecific antibodies (BsAbs) have emerged as a leading drug class for cancer therapy and are becoming increasingly of interest for therapeutic applications. As of April 2020, over 123 BsAbs are under clinical evaluation for use in oncology (including the two marketed BsAbs Blinatumomab and Catumaxomab). The majority (82 of 123) of BsAbs under clinical evaluation can be categorized as bispecific immune cell engager whereas a second less well-discussed subclass of BsAbs targets two tumor-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 84 publications
1
39
0
1
Order By: Relevance
“…The incidence of severe toxicity and toxicityrelated discontinuations were low despite a lack of selectivity against the wild-type EGFR, suggesting that the bispecific nature of amivantamab may affect the safety profile, potentially through altered target cell selectivity (eg, tumor cells). 21,29,30 Early efficacy in this study identified clinically significant monotherapy activity of amivantamab in EGFR Exon20ins NSCLC in the chemotherapy-naive (n 5 10) and chemotherapy-relapsed setting (n 5 29). This experience led to Breakthrough Therapy Designation in both the United States and China for the latter population on the basis of the investigator-assessed ORR of 41%, the median DOR of 7 months, and the CBR of 72%.…”
Section: Discussionmentioning
confidence: 90%
“…The incidence of severe toxicity and toxicityrelated discontinuations were low despite a lack of selectivity against the wild-type EGFR, suggesting that the bispecific nature of amivantamab may affect the safety profile, potentially through altered target cell selectivity (eg, tumor cells). 21,29,30 Early efficacy in this study identified clinically significant monotherapy activity of amivantamab in EGFR Exon20ins NSCLC in the chemotherapy-naive (n 5 10) and chemotherapy-relapsed setting (n 5 29). This experience led to Breakthrough Therapy Designation in both the United States and China for the latter population on the basis of the investigator-assessed ORR of 41%, the median DOR of 7 months, and the CBR of 72%.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, we have witnessed much progress with bsAb technologies and therapeutics as reviewed here and elsewhere ( 13 , 71 ), which have found wide applicability to immunotherapy for cancer treatment. And thus, many bsAb constructs with differing mechanisms of action are being investigated, each with their own limitations and advantages.…”
Section: Discussionmentioning
confidence: 99%
“…BsAbs can target two specific antigens or different areas of the same antigen at the same time (114) HER2, also known as neu, ErbB-2, CD340, and p185, is a member of the ERBB family of receptor tyrosine kinases. This family also includes ERBB1, ERBB3, and ERBB4.…”
Section: Blocking Of Dual Signaling Pathwaysmentioning
confidence: 99%
“…BsAbs can target two specific antigens or different areas of the same antigen at the same time ( 114 ). Blocking signal transmission along signal pathways can affect the occurrence and development of tumors, target the tumor microenvironment, and inhibit the regeneration of tumor blood vessels.…”
Section: Mechanisms Of Action Of Bsabsmentioning
confidence: 99%